An assessment of an instrument with which to conduct internal audits - Kasim M.A.B.; Bt Mohd Hanafi S.R.; Aziz A.A.; Hancock D.R. (Nova Science Publishers, Inc., 2023)
As a result of the financial demise of several international corporations in recent years, the need for competent internal audits has received significant attention. Although most corporations conduct internal audits, their effectiveness has often been suspect and many of the existing instruments with which to measure internal audit effectiveness have severe limitations. Development of the new instrument to quantitatively measure the effectiveness of internal audit functions is clearly needed. This study uses the Internal Audit Professional Practice Framework to examine the validity and reliability of a new instrument with which to conduct internal audits. The results suggest that the instrument is highly reliable and conforms to the standards established by the Institute of Internal Auditors -- the professional organization governing the internal auditing profession. 2009 Nova Science Publishers, Inc. All rights reserved.